“Mit Computern kenne ich mich eigentlich nicht aus …” - Spangenberg, L.; Forkmann, T.; Glaesmer, H. (Nervenheilkunde, 2014)
Objective: Self-report data is increasingly gathered by electronic devices. The present study aimed at testing usability and patient acceptance of two administration modes (tablet vs. paper-pencil) in primary care patients _ 60 years. Material and methods: Two depression instruments were administered using a randomized crossover design (n = 193). Results: Patients positively evaluated the usability of the tablet (clear presentation, well manageable). Additionally, the majority of patients preferred the tablet over the paper-pencil mode (more suitable, less stressful and difficult). Tablet mode and increasing age were associated with increased response time. Age, somatic morbidity and formal education showed only weak associations with usability and acceptance. Conclusion: Socio-demographic variables such as increasing age and formal education and somatic morbidity do not lead to limitations of use. Clinical relevance: The study demonstrates high usability and acceptance of depression assessment by tablets in elderly patients.
Keywords: Tablet; Ältere; Benutzerfreundlichkeit; Akzeptanz